Improving quality of leisure environment considering youth preferences in Mashhad, Iran - Hasanpour, Sahar; Khakzand, Mehdi; Faizi, Mohsen (Frontiers in Built Environment, 2023)
With the industrialization of societies, urban planners are more concerned with the significance of leisure time since it affects individuals’ mental state and well-being. Considering the importance of visual quality, this study examined young adults in the Torghabe and Mellat park of the Mashhad to improve the quality of the leisure environment by detecting youth preferences for natural and man-made variables. Accordingly, the classic Delphi method was used to detect research variables. The most common preference priorities were extracted by photo surveys, simulation of the study environment, and conjoint analysis with the full design approach to calculate the relative importance and Part-Worths, or utility values of these variables, according to the results, among the considered attributes, "shape" (32.61%) and " solid/void patterns" (5.96%) were of the most and the least significance in the youth preferences for leisure spaces combining natural and shopping environment.